Kalimat Hubungan Paradigmatik dan Sintagmatik dalam Novel Before the Coffee Gets Cold - Sugiyanti, Neni (Jurnal Humaniora dan Ilmu Pendidikan, 2024)
Purpose: This study aims to analyse the syntagmatic and paradigmatic relationships in the novel Before the Coffee Gets Cold by Toshikazu Kawaguchi, focusing on how the linguistic elements in the novel construct deep and complex meanings. Research methodology: The method used in this study is a qualitative approach with in-depth text analysis, including the collection of key quotations from the novel that are then analysed syntagmatically and paradigmatically. Results: The results reveal that Kawaguchi's use of the syntagmatic relationship helps build a coherent and structured plot, while the paradigmatic relationship enriches meaning through word choices that carry connotations and symbolism related to the novel’s main themes. These results offers new insights into literary and linguistic studies, particularly in understanding how language structure reinforces emotional and thematic messages in narratives. Conclusion: The novel portrays time as a medium for emotional reflection, using structure and meaning to convey themes of regret, acceptance, and the value of each moment. Limitations: The research is based solely on the English translation of the novel, which may result in interpretative differences due to language and cultural nuances. Contribution: This research is valuable in several areas and disciplines. In linguistics, it contributes to the study of structural linguistics. In literary studies, the analysis provides insights into how linguistic structures influence storytelling, it can be applied in education, particularly in teaching literature and linguistics.